(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the rate of target achievement of LDL-C in high and very high cardiovascular risk patients. Methods: A retrospective study of cardiology outpatient database in Nhan dan Gia Dinh Hospital from 2020 January to 2021 January was conducted. Prescriptions before and after lipid investigation were collected to consider the statin prescription behavior. Results: LDL-C targets were achieved in 29.17% and 8.24% of high risk and very high risk patients, respectively. A majority (83.46%) were on intermediate intensity and 16.54% were on high intensity statin treatment. Statin dose increment rate was 23.21% in unachieved LDL-C patients. Conclusion: LDL-C achievement rates were modest in high and very high cardiovascular risk patients while the statin prescription was not adequate.